Metal jewellery of the Southern Levant and its Western neighbours cross-cultural influences in the Early Iron Age Eastern Mediterranean - Verduci, Josephine A. (Peeters, 2018)
The Early Iron Age period of the southern coastal plain of the Levant (ca. 1200-900 BCE) displays certain new features that suggest the appearance of the Philistines or other Sea Peoples. The early stages of this period represent a departure from Late Bronze Age traditions and evidence of cross-cultural influences within the eastern Mediterranean. This volume contributes to the discussion of the origin of the Sea Peoples by examining the role of adornment in the portrayal of cultural identity. Metal jewellery is assessed from 29 sites in the southern Levant, the Aegean, and Cyprus, resulting in the creation of the first multi-regional typology of metal jewellery for the Iron Age I-IIA eastern Mediterranean. By examining various categories of metal jewellery from the southern Levant and its western neighbours, this study contributes to the debate about the relations and exchanges that affected the region during this pivotal period in history. The formation, maintenance, and communication of group identification through physical appearance is assessed through a phenomenological view of cultural material to explain what is termed cultural intention
Keywords: Eisenzeit; Schmuck; Mittelmeerraum; Jewelry, Ancient / Mediterranean Region; Jewelry, Ancient; Mediterranean Region